2016
DOI: 10.13189/ujer.2016.040819
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Elementary School Teachers on Outdoor Education

Abstract: Outdoor education stands out as one of the methods to deliver the desired educational outcomes taking the needs of the students, teachers and the curricular objectives into consideration. Outdoor education focuses on experimental, hands-on learning in real-life environments through senses, e.g., through visual, auditory, and tactile means, improving students' learning and retention of knowledge as a result. Appropriate sites outside of the classroom and school environment are chosen as the setting for outdoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…They found that while 93% of the teachers included a period of outdoor play in their daily routine, 70% indicated that this time outdoors was short (15-30 minutes a day). In a similar study done in Turkey (Palavan et al, 2016), twothirds of teachers interviewed said they had never heard of outdoor education before, and had a list of reasons why they did not regularly engage in outdoor learning with students. These reasons included concerns over safety, curriculum deadlines, difficulty in access, a perceived lack of parent support, and even laziness (Palavan et al, 2016).…”
Section: Limited Use Of Olesmentioning
confidence: 96%
See 1 more Smart Citation
“…They found that while 93% of the teachers included a period of outdoor play in their daily routine, 70% indicated that this time outdoors was short (15-30 minutes a day). In a similar study done in Turkey (Palavan et al, 2016), twothirds of teachers interviewed said they had never heard of outdoor education before, and had a list of reasons why they did not regularly engage in outdoor learning with students. These reasons included concerns over safety, curriculum deadlines, difficulty in access, a perceived lack of parent support, and even laziness (Palavan et al, 2016).…”
Section: Limited Use Of Olesmentioning
confidence: 96%
“…Outdoor Learning Environments (OLEs) provide opportunities for such hands-on, experimental learning in real-life environments and the development of environmental awareness (Palavan, Cicek, & Atabay, 2016). OLEs can provide "multi-sensory, movement-based, holistic and stimulating experiences" (White, 2011, p. 7), can enhance the levels of creativity children use in their play (Fjortoft, 2001), and have the potential to contribute to the well-being, health, and development of young children (Cooper, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In carrying out his professional duties, a teacher is obliged as follows. First, planning to learn, carrying out quality learning processes, and assessing and evaluating learning outcomes (Palavan et al, 2016). Second, improving and developing academic qualifications and competencies on an ongoing basis in line with science, technology, and the arts.…”
Section: Field Experience Practice Program (Ppl) Is a Faculty Of Teacher Training Andmentioning
confidence: 99%
“…Trabalhar o conhecimento a partir de um contexto é perceber a "indissociabilidade do todo" e que abordagens multi e transdisciplinares na construção deste conhecimento são imprescindíveis. As relações estabelecidas entre a ação/experiência e suas consequências, ou seja, sua contextualização é o que proporciona uma real aprendizagem (PALAVAN et al, 2016).…”
Section: Introductionunclassified